Ethanol Administration Produces Divergent Changes in GABAergic Neuroactive Steroid Immunohistochemistry in the Rat Brain. (26th July 2013) - Cook, Jason B.; Dumitru, Ana Maria G.; O'Buckley, Todd K.; Morrow, A. Leslie
<x xml:space="preserve">Abstract</x> Background The 5α‐reduced pregnane neuroactive steroid (3α, 5α)‐3‐hydroxypregnan‐20‐one (3α, 5α‐THP or allopregnanolone) is a potent positive modulator of GABAA receptors capable of modulating neuronal activity. In rats, systemic ethanol (EtOH) administration increases cerebral cortical and hippocampal levels of 3α, 5α‐THP, but the effects of EtOH on 3α, 5α‐THP levels in other brain regions are unknown. There is a large body of evidence suggesting that 3α, 5α‐THP enhances EtOH sensitivity, contributes to some behavioral effects of EtOH, and modulates EtOH reinforcement and motivation to drink. In this study, we used immunohistochemistry (IHC) to determine EtOH‐induced changes in cellular 3α, 5α‐THP expression in brain regions associated with EtOH actions and responses. Methods Male Wistar rats were administered EtOH (2 g/kg) or saline intraperitoneally and after 60 minutes transcardially perfused. IHC was performed on free‐floating sections (3 to 4 sections/animal/brain region) using an affinity purified anti‐3α, 5α‐THP primary antibody, and immunoreactivity was visualized with 3, 3′‐diaminobenzidine. Results EtOH significantly increased 3α, 5α‐THP immunoreactivity by 24 ± 6% in the medial prefrontal cortex, 32 ± 12% in the hippocampal Cornu Ammonis area 1 (CA1) pyramidal cell layer, 52 ± 5% in the polymorph cell layer of the dentate gyrus (DG), 44 ± 15% in the bed nucleus of the stria terminalis, and 36 ± 6% in the paraventricular nucleus of the hypothalamus. In contrast, EtOH administration significantly reduced 3α, 5α‐THP immunoreactivity by 25 ± 5% in the nucleus accumbens "shore" and 21 ± 3% in the central nucleus of the amygdala. No changes were observed in the ventral tegmental area, dorsomedial striatum, granule cell layer of the DG, or the lateral and basolateral amygdala. Conclusions The results suggest acute EtOH (2 g/kg) produces divergent, brain region specific, effects on cellular 3α, 5α‐THP levels. Regional differences in the effects of EtOH suggest there may be regional brain synthesis of 3α, 5α‐THP independent of the adrenal glands and novel mechanisms that reduce cellular 3α, 5α‐THP. Regional differences in EtOH‐induced changes in 3α, 5α‐THP levels likely contribute to EtOH effects on neuronal function in brain.